COMPLUTENSE UNIVERSITY OF MADRID: Impressions - de Gavieres, Forelle; Khalmatova, B.T.; Okhunov, A.O.; Atakov, S.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The Complutense University of Madrid is a public research university located in Madrid. Founded in Alcal in 1293 (before relocating to Madrid in 1836), it is one of the oldest operating universities in the world. It is located on a sprawling campus that occupies the entirety of the Ciudad Universitaria district of Madrid, with annexes in the district of Somosaguas in the neighbouring city of Pozuelo de Alarcon. It is named after the ancient Roman settlement of Complutum, now an archaeological site in Alcala de Henares, just east of Madrid. It enrols over 86,000 students, making it the third-largest non-distance European university by enrollment. It is one of the most prestigious Spanish universities and consistently ranks among the top universities in Spain, together with the University of Barcelona, Pompeu Fabra University, UAM, and UAB in International and European league tables and surveys. Since its foundation, it has attracted numerous scholars, intellectuals and students from all over Spain and the world, establishing itself as one of the main international centres of learning. By the Royal Decree of 1857, the University of Madrid was the first and only institution in Spain authorized to grant doctorate degrees throughout the Spanish Empire. In 1909, the University of Madrid became one of the first universities in the world to grant a doctorate degree to a woman. In the Shangai Ranking, the UCM is ranked among the best 300 worldwide, and among the top 3 Spanish ones. In the QS World University Ranking, the UCM is #226 worldwide, #85 in Europe, and #4 in Spain. In the Scimago institution rankings, the UCM is #175 worldwide, #79 in research, and #3 in Spain. Besides, internationally it is in the top 3% overall, in the top 2% in research, and top 3% in social impact.